(untitled) (Zoo Botanica, 2025)
Sugar beet (Beta vulgaris) is a biennial herbaceous crop with important agricultural and therapeutic uses. The present study aims to evaluate phytochemical constituents in two varieties (V1 = local variety, V2 = red sugar beet, obtained from Agriculture Department Skardu) grown under two conditions at Skardu, including the farmer field (FF) and experimental field (EF). Plant samples (n=03) including leaves and tuber were collected from each location and analyzed for total phenolic content (TPC), total flavonoid content (TFC), total anti-oxidant capacity (TAC), total reducing power (TRP) and free radical scavenging assay (DPPH). Results obtained were tested for significance (ANOVA and LSD) by using statistical software package (Statistix 8.1, USA). The results revealed that highest phenolic content was found in leaves of V2 experimental field (48.94 ± 0.7 μg GAE/mg), whereas higher TFC was found in tubers of V1 at experimental field (47.98 ± 0.99 μg QE/mg), and TRP was maximum in leaves of V2 at experimental field (209.64 ± 0.89 μg AAE/mg). The highest antioxidant capacity was recorded in the leaves of V1 under experimental field conditions (103.63 ± 1.73 μg AAE/mg), while the maximum DPPH radical scavenging activity was observed in the leaves of V2 at farmer field conditions (44.16 ± 0.88%). The ANOVA test revealed significant differences (p < 0.05) in the levels of TAC, TFC, TPC, TRP and DPPH activities in tested samples. This study provides novel insights into the phytochemical composition of Beta vulgaris grown under two contrasting conditions, demonstrating that agronomic practices in the experimental field significantly influenced the phytochemical profiles across different varieties. Such variations in chemical constituents not only elaborate the potential role of sugar beet as functional food grown at highlands of Skardu, but also elucidate its ability to cope under the stressful conditions. Both varieties of sugar beet grown under experimental field conditions exhibited enhanced productivity and bioactive potential, underscoring its value as a functional food crop for sustainable mountain agriculture.